Taller de Trabajo sobre Cratylia (1995, Brasília, D.F., Brasil). Potencial del género Cratylia como leguminosa forrajera : Memorias - Pizarro, Esteban A.; Coradin, Lídio (International Center for Tropical Agriculture, 1996)
The Cratylia genus comprises drought-tolerant legumes that are rich in proteins. It can be exploited as food for humans and fodder for animals living in semiarid areas such as Northeast Brazil. This ecologically plastic genus (characterized by homeostasis during development) is also adapted to the Brazilian Cerrados and certain niches in the Amazon Basin. Brazil currently has programs to study this native germplasm to prevent its genetic erosion and to strategically increase the country?s offer of products for its population?s direct or indirect consumption. This would reduce the high use (already at 80%) of exotic species. A symposium was held in July 1995, in Brasília, DF, under the sponsorship of EMBRAPA, CENARAGEN, and CIAT, and with the participation of other institutions. Its theme was on the collaboration for research on aspects ranging from the genus?s geographical distribution, through applying biotechnology for its improvement, and final uses. The proceedings were published by CIAT, in May 1996, under the title Potencial del Género Cratylia como Leguminosa Forrajera [The Potential of the Cratylia Genus as Forage Legumes]